2011
DOI: 10.3109/09553002.2011.560993
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects human cells from clustered DNA damages, killing and acquisition of soft agar growth induced by X-rays or 970 MeV/n Fe ions

Abstract: Melatonin's effective reduction of radiation-induced critical DNA damages, cell killing, and striking decrease of transformation suggest that it is an excellent candidate as a countermeasure against radiation exposure, including radiation exposure to astronaut crews in space travel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…(76–78)] and fruit extracts (79, 80). In addition, there are a number of new potential cancer preventive agents that have been shown to mitigate in vitro SEBs of the space radiation cancer risk; examples include melatonin (81) and a synthetic triterpenoid, bardoxolone methyl, which protects against space radiation-induced transformation of human colon epithelial cells (82). …”
Section: Introductionmentioning
confidence: 99%
“…(76–78)] and fruit extracts (79, 80). In addition, there are a number of new potential cancer preventive agents that have been shown to mitigate in vitro SEBs of the space radiation cancer risk; examples include melatonin (81) and a synthetic triterpenoid, bardoxolone methyl, which protects against space radiation-induced transformation of human colon epithelial cells (82). …”
Section: Introductionmentioning
confidence: 99%
“…The results of a recent study published by Das and colleagues [84] also emphasize the high efficacy of melatonin in abating molecular damage inflicted by ionizing radiation. In this case, melatonin (0.0-3.5 mM) was mixed in a solution of supercoiled plasmid DNA and the samples were then irradiated in the cold with either 0.15 or 25 Gy of X-rays (100 kVp) delivered by a Phillips Xray machine at a dose rate of 0.9 Gy/min.…”
Section: Melatonin As a Radioprotector: In Vitro Studiesmentioning
confidence: 86%
“…Melatonin also has a very long shelf-life and is inexpensive. To re-emphasize its high efficacy as a radioprotective agent, after a series of sophisticated tests of melatonin as a radiation protector at the Brookhaven National Laboratory in the United States, the authors of the published report concluded that melatonin ''is an excellent candidate as a countermeasure against radiation exposure'' [84].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations